Association Between Maternal Serum Ferritin Concentration and Risk of Gestational Diabetes Mellitus and Adverse Fetal Outcomes - Nadia Naheed; Sadia Majeed; Ayesha Iqbal; Lubna Noor; Bushra Gull; Javaria Majeed; Syed Awais Attique (Pakistan Journal of Health Sciences, 2026)
Gestational diabetes mellitus (GDM) is a common pregnancy-related metabolic disorder linked to serious maternal and fetal complications. Rising evidence indicates that elevated maternal iron stores, especially serum ferritin, may contribute to GDM and adverse neonatal outcomes, yet data from South Asia, particularly Pakistan, are limited. Objectives: To evaluate the association between maternal serum ferritin concentrations at different gestational ages and the risk of GDM and adverse fetal outcomes. Methods: A retrospective cohort study of 146 singleton pregnancies at Combined Military Hospital Multan measured ferritin at 16–18 and 28–32 weeks. Participants were categorized into ferritin quartiles, GDM was diagnosed via a 75-g Oral Glucose Tolerance Test (OGTT), and logistic regression assessed associations after adjusting for key maternal covariates. Results: Higher mid-gestation serum ferritin levels demonstrated a significant relationship with increased risk of GDM (adjusted OR for Q4 vs. Q1: 1.43; p=0.016). Elevated ferritin was also linked to macrosomia (adjusted odds ratio (AOR)=2.01; 95% confidence interval (CI): 1.09–3.67), large for gestational age (LGA) infants (AOR=2.01; 95% CI: 1.09–3.72), and increased neonatal head circumference (AOR=2.70; 95% CI: 1.53–4.77). Although higher ferritin levels were associated with a reduced risk of small for gestational age (SGA) (AOR=0.44; 95% CI: 0.17–1.17), this association was not statistically significant. In late pregnancy, ferritin showed an inverse relationship with macrosomia, suggesting time-dependent effects. Conclusions: Elevated maternal serum ferritin levels during mid-pregnancy are associated with an increased risk of GDM and fetal overgrowth outcomes.